FENOMENA KOMUNIKASI WARIA DI KOTA BAGANSIAPIAPI KABUPATEN ROKAN HILIR - ", Irwandis; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Shemale in fact socially ostracized by the community, this is because that transvestites pass things that are contrary to the common view and religion. On the one hand should be placed as a social reality that is not inevitable existence.This study uses qualitative research with phenomenological approach. Subjects consisted of five transgender people in the city Bagansiapiapi selected by using purposive. The study used data collection techniques in-depth interviews, observation, and documentation study. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed first, transvestites City Bagansiapiapi motif consists of a motive for (Because motive) that is stuck in the wrong spirit, trauma, lack of parental attention, and economic demands. While the motive (in order to motive) that wants to be a normal man, remains a drag queen, and want to be recognized presence in the community. Second, the meaning that is given to him that transsexuals felt himself despised, merrasa he resigned and felt sorry. Third, the communication experience categorized into two pleasant communication experience in the form of a good reception from the family, affection and attention gained from the pair, non-discrimination and their support. And communications experience unpleasant form of satire and taunts from family, romance and the threat of conflict jeers and insults from the neighborhood.Keyword : phenomenon , Shemale, motive, meaning, communication experience